ISLAM DI CINA - Najamuddin, Najamuddin (Tasamuh: Jurnal Studi Islam, 2016)
Religion of Islam has been present in China since the year 650, precisely during the reign of the Tang Dynasty. At that time, one of the companions of the Prophet, namely Saad ibn Abi Waqqas came to mainland China to convey the message of the Prophet and Islam introduced to the people of the land. Since then, Islam widespread in China mainly through trade intermediaries. The development of Islam in China has gone through by several dynasties, including the Tang, Wudai, Song Dynasty, Yuan Dynasty, Qing Dynasty and the Ming Dynasty. But among these there is mentioned dynasty that has developed very rapidly and some are experiencing sluggish growth journey. Islam in China was originally foreign Muslims who were able to assimilate with the Chinese community. At a later stage, some magnifying dynasty in China and other tribes embraced Islam. Then they set up a mosque and always are steadfast personality. Karen case, Islam in China still exists. The downside is that the communists in Russia and so did China that killed millions of people is a bitter memory. The plus side is due to the attitude of the West communists identical with the cause of Islam rose to fight for their rights. On the other hand, the defeat of the Soviet Union, whose influence penetrated into China in the ideological war with the United States, causing the nationâs Muslim minority gets fresh air to rise and strengthen its existence.